Histological Characterization of the Dicer1 Mutant Zebrafish Retina - Saeed Akhtar; Sarita Rani Patnaik; Rakesh Kotapati Raghupathy; Turki M. Al-Mubrad; John A. Craft; Xinhua Shu (Journal of Ophthalmology)
DICER1, a multidomain RNase III endoribonuclease, plays a critical role in microRNA (miRNA) and RNA-interference (RNAi) functional pathways. Loss of Dicer1 affects different developmental processes. Dicer1 is essential for retinal development and maintenance. DICER1 was recently shown to have another function of silencing the toxicity of Alu RNAs in retinal pigment epithelium (RPE) cells, which are involved in the pathogenesis of age related macular degeneration. In this study, we characterized a Dicer1 mutant fish line, which carries a nonsense mutation (W1457Ter) induced by N-ethyl-N-nitrosourea mutagenesis. Zebrafish DICER1 protein is highly conserved in the evolution. Zebrafish Dicer1 is expressed at the earliest stages of zebrafish development and persists into late developmental stages; it is widely expressed in adult tissues. Homozygous Dicer1 mutant fish (DICER1W1457Ter/W1457Ter) have an arrest in early growth with significantly smaller eyes and are dead at 14–18 dpf. Heterozygous Dicer1 mutant fish have similar retinal structure to that of control fish; the retinal pigment epithelium (RPE) cells are normal with no sign of degeneration at the age of 20 months.